Capacidade funcional de idosos: implicações para atividades instrumentais de vida diária - George Luiz Alves Santos; Rosimere Ferreira Santana (Universidade Federal do Ceará, 2017)
Objective: to describe the implications of social and cultural factors for instrumental activities of daily living of elderly people who participate of an interaction group. Methods: qualitative study, of ethno-nursing type, performed with 35 elderlies of a university extension project. Data collection was based on on-site observations, field journal and interviews. Analysis of the data was carried out in four phases proposed by ethno-nursing. Results: information technology, mobile telephones, accessibility to urban space, low education levels, as well as the slowness associated with the aging process influenced daily activities performance and impact on their functional capacity. Conclusion: cultural values and ways of life were expressed in daily habits that characterized the old way of being, a gerontology culture. Political, legal, friendship and social factors were described.